An Investigation of q-Rung Orthopair Fuzzy Subgroups and Fundamental Isomorphism Theorems (European Journal of Pure and Applied Mathematics, 2025)
The q-rung orthopair fuzzy set (q-ROFS) has been developed as an extension of the Pythagorean fuzzy set (PFS) to address ambiguity in various decision-making contexts. Group theory is a significant area of mathematics with numerous applications across various scientific fields. This paper examines q-rung orthopair fuzzy group theory, emphasizing the importance of q-ROFS and group theory. The concept of a q-rung orthopair fuzzy subgroup (q-ROFSG) is introduced, and its various algebraic properties are examined. A comprehensive investigation into q-rung orthopair fuzzy cosets (q-ROFCs) and q-rung orthopair fuzzy normal subgroups (q-ROFNSGs) has been conducted. The definitions of q-rung orthopair fuzzy homomorphism and isomorphism are presented. We extend the concept of the quotient group of a classical group V in relation to its normal subgroup U by introducing a q-ROFSG of V⁄U. The q-rung orthopair fuzzy variant of the three fundamental isomorphism theorems has been demonstrated.